Oregano essential oil-pectin edible films as anti-quorum sensing and food antimicrobial agents - Alvarez, Maria V.; Ortega-Ramirez, Luis A.; Gutierrez-Pacheco, M. Melissa; Bernal-Mercado, A. Thalia; Rodriguez-Garcia, Isela; Gonzalez-Aguilar, Gustavo A.; Ponce, Alejandra; Moreira, Maria del R.; Roura, Sara I.; Ayala-Zavala, J. Fernando (Frontiers in Microbiology, 2014)
Edible films can be used as carriers for antimicrobial compounds to assure food safety and quality; in addition, pathogenesis of food bacteria is related to a cell to cell communication mechanism called quorum sensing (QS). Oregano essential oil (OEO) has proved to be useful as food antimicrobial; however, its food applications can be compromised by the volatile character of its active constituents. Therefore, formulation of edible films containing OEO can be an alternative to improve its food usages. QS inhibitory activity of OEO and pectin-OEO films was evaluated using Chromobacterium violaceum as bacterial model. Additionally, antibacterial activity was tested against Escherichia coli O157:H7, Salmonella Choleraesuis, Staphylococcus aureus, and Listeria monocytogenes. OEO was effective to inhibit bacterial growth at MIC of 0.24 mg/mL for all tested bacteria and MBC of 0.24, 0.24, 0.48, and 0.24 mg/mL against E. coli O157:H7, S. Choleraesuis, S. aureus, and L. monocytogenes, respectively. Pectin-films incorporated with 36.1 and 25.9 mg/mL of OEO showed inhibition diameters of 16.3 and 15.2 mm for E. coli O157:H7; 18.1 and 24.2 mm for S. Choleraesuis; 20.8 and 20.3 mm for S. aureus; 21.3 and 19.3 mm for L. monocytogenes, respectively. Pectin-OEO film (15.7 mg/mL) was effective against E. coli O157:H7 (9.3 mm), S. aureus (9.7 mm), and L. monocytogenes (9.2 mm), but not for S. Choleraesuis. All concentrations of OEO (0.0156, 0.0312, 0.0625 and 0.125 mg/mL) and pectin-OEO films (15.7, 25.9 and 36.1 mg/mL) showed a significant anti-QS activity expressed as inhibition of violacein production by C. violaceum. Additionally, the application of pectin-OEO films was effective reducing total coliforms, yeast, and molds of shrimp and cucumber slices stored at 4 °C during 15 d. These results demonstrated the potential of pectin films enriched with OEO as food related microorganisms and QS inhibitors.